The Comparison Between the Hungarian and Romanian National Security Strategies - Veress, Csongor Balazs (European Scientific Journal, ESJ, 2022)
In 2020 first Hungary, later Romania, two member states of NATO, EU and PESCO adopted their own Nation Security Strategies. There was a need in both mentioned countries for new defense strategies because in recent years new challenges and threats have emerged, like the annexation of Crimea, the destabilization of Ukraine, and the migration crisis. These documents describe the two countries’ place in the international system, list the threats and challenges to their security, and finally try to give a solution based on their possibilities and capabilities. The strategies also carry a message to neighbors, allies, and future rivals. The document’s aim is the protection of core national values. In this paper, my goal is to offer an overview of the strategic documents and to analyze first the Romanian National Defense Strategy. The Hungarian National Security Strategy, and finally to highlight the similarities and find the differences like national sovereignty, protection of Christian values, or the importance of a European army. In both security documents old and new threats appear like terrorism, climate change, migrant problems, hybrid warfare, arms, and drug trafficking. Each strategy is an official communication tool, an official policy message to external and internal actors at different levels and of different types that influence national security. To achieve my goal, I used the methods of document analysis and content analysis on the primary sources. The purpose of the research is to compare two neighboring countries’ strategies, and how they react to their national threats.